Penentuan Jenis Kelamin berdasarkan Sidik Hypothenar - Widya Iswara, Raja Al Fath; Rohmah, Intarniati Nur; Santosa, Santosa; Relawati, Ratna (RSUP Dr. Kariadi, 2020)
Background : Hypothenar regio in palmar is an area that is often contact with surfaces while doing the activity which can establish print or pattern of protruding line (ridge) that can be used in identification process. One of the important identification to sex determination. The aims of this study is to sex determination based on hypothenar print. Methods : The study was a cross sectional study. Subjects were 300 students underwent clinical clerkship in Forensic and Medicolegal Dr. Kariadi Semarang hospital during October-December 2017, age 21-26 years, male (n = 150) and female (n = 150). Hypothenar print measured by calculating the average number of ridge hypothenar palm on the side of the top, middle and bottom in each area measuring 5 mm x 5 mm. A Mann-Whitney test was performed to analyze the the difference between left and right hypothenar ridge. Spearman correlation test was conducted to measure the association of hypothenar prints and sex. Results : In male, the average number of hypothenar ridge on the right palm was 10 (7-12)/25 mm2, while the left palm 10 (7-13)/25 mm2. In female, the average number of hypothenar ridge on the right palm was 12 (8-16)/25 mm2, while the left hand was 12 (8-16)/25 mm2. The was a significant difference between the right hand hypothenar ridge (p = 0.008) and the left hand hypothenar ridge (p = 0.017) between male and female. There was a significant correlation between hypothenar prints and sex (p = 0.000). Conclusion : Hypothenar prints can be use in sex determiation where female have more hypothenar ridge count and density than male.